Electrophysiological alterations in a murine model of chronic coxsackievirus B3 myocarditis. - Sven Kaese; Robert Larbig; Matthias Rohrbeck; Gerrit Frommeyer; Dirk Dechering; Jan Olligs; Sabine Schönhofer-Merl; Rainer Wessely; Karin Klingel; Guiscard Seebohm; Lars Eckardt (PLoS ONE)
Introduction Coxsackievirus B3 (CVB3) is known to induce acute and chronic myocarditis. Most infections are clinically unapparent but some patients suffer from ventricular arrhythmias (VA) and sudden cardiac death (SCD). Studies showed that acute CVB3 infection may cause impaired function of cardiac ion channels, creating a proarrhythmic substrate. However, it is unknown whether low level CVB3+ expression in myocytes may cause altered cardiac electrophysiology leading to VA. Methods Cellular electrophysiology was used to analyze cellular action potentials (APs) and occurrence of afterdepolarizations from isolated cardiomyocytes of wildtype (WT) and transgenic CVB3ΔVP0 (CVB3+) mice. Further, we studied surface ECGs, monophasic APs, ventricular effective refractory period (VERP) and inducibility of VAs in Langendorff-perfused whole hearts. All used cardiomyocytes and whole hearts originated from male mice. Results Cellular action potential duration (APD) in WT and CVB3+ myocytes was unchanged. No difference in mean occurrence or amplitude of afterdepolarizations in WT and CVB3+ myocytes was found. Interestingly, resting membrane potential in CVB3+ myocytes was significantly hyperpolarized (WT: -90.0±2.2 mV, n = 7; CVB3+: -114.1±3.0 mV, n = 14; p<0.005). Consistently, in Langendorff-perfused hearts, APDs were also not different between WT and CVB3+ whole hearts. Within both groups, we found a heart rate dependent shortening of ADP90 with increasing heart rate in Langendorff-perfused hearts. VERP was significantly prolonged in CVB3+ hearts compared to WT (WT: 36.0±2.7 ms, n = 5; CVB3+: 47.0±2.0 ms, n = 7; p = 0.018). Resting heart rate (HR) in Langendorff-perfused hearts was not significantly different between both genotypes. Electrical pacing protocols induced no VA in WT and CVB3+ hearts. Conclusion In CVB3+ mice, prolonged ventricular refractoriness and hyperpolarized resting membrane potentials in presence of unchanged APD were observed, suggesting that low level CVB3 expression does not promote VA by altered cardiac electrophysiology in this type of chronic myocarditis. These findings may suggest that other mechanisms such as chronic myocardial inflammation or fibrosis may account for arrhythmias observed in patients with chronic enteroviral myocarditis.